Implementation of Handheld Fan Therapy to Alleviate Shortness of Breath in Patients with Congestive Heart Failure (CHF) - Mia Sasmita Atmaja; Suci Amin (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
One of the common issues faced by individuals with heart failure is an ineffective breathing pattern, which primarily leads to shortness of breath. Non-pharmacological therapy presents a lower risk and, while not a substitute for medication, can help alleviate ineffective breathing patterns. In patients with congestive heart failure (CHF), one such non-pharmacological approach is handheld fan therapy. This study aims to evaluate the application of handheld fan therapy in reducing shortness of breath among CHF patients at Bengkalis District Hospital. The research employs a descriptive quantitative case study design, with 12 CHF patients selected through a consecutive sampling technique. Univariate data analysis revealed that before receiving handheld fan therapy, the average respiratory rate of CHF patients was 31.40 breaths per minute, with a maximum of 32.71 breaths per minute and a minimum of 30.40 breaths per minute. After the therapy, the average respiratory rate decreased to 29.9 breaths per minute, with a maximum of 30.90 breaths per minute and a minimum of 28.40 breaths per minute.